Peraturan Desa dan Otonomi Desa Potret di Kecamatan Pemayung Jambi - Elita Rahmi; Hartarti Hartarti; Fitria Fitria (Wajah Hukum, 2023)
Village regulations (Perdes) are often made haphazardly due to the problem of minimal human resources, making it difficult to know what the village wants in realizing village autonomy. Making Village Regulations a form of village autonomy needs to be more understood by village officials, the Village Consultative Body, and the village community. Village regulations manifest the village as a legal community unit with the right to regulate and manage its household. The difficulty in making Perdes is because the legislator must master several sciences, particularly the science of legislation, knowledge of local government, and knowledge of village administration and other sciences so that Perdes do not conflict with higher regulations and not conflict with the public interest. This writing aims to provide knowledge to village officials, the Village Consultative Body, and village communities to "literate Perdes" or have a sense of curiosity about Perdes, both in terms of authority and substance and procedures for making Village Regulations. The socialization method used is a simulation, Brainstorming, lecture, and question. In conclusion, Village Regulation Making Training must be carried out continuously because it requires knowledge and skills to understand the legal product's philosophical, sociological, and juridical aspects in the form of a Perdes. Second, the drafting of Perdes is an integral part of the administration of village, sub-district, and district government, so it is necessary to form a Perdes of Batanghari district related to the mechanism for making Perdes as a guideline for villages in exploring village potential.